Spectroscopic Characterizations of Sediment in Karanrang Island (Spermonde Archipelago) using FT-IR, XRF and XRD - Firman, Nur Faiizah Aqiilah; Armus, Rakhmad; Maming; Zakir, Muhammad; Permatasari Hasra, Adji; Fuad Fathurahman, Achmad (Al-Kimia, 2024)
Research about spectroscopic characterizations of sediment in Karanrang Island has been carried out. This research aimed to determine the content of mineral in sediment before doing further research (measurement 14C activity in sediment). Sediment sampling was conducted in the middle of the island with a depth of 0.5; 1.0 and 1.5 m. Sediment was analysed by Fourier-transform infrared (FT-IR), X-ray fluorescence (XRF) and X-ray diffraction (XRD). Based on the analysis, minerals were found lime (CaO), aragonite (CaCO3), silicon (Si), quartz (SiO2), strontium (Sr) and strontium oxide (SrO). Minerals contained in sediment are CaO (11.02; 11.20 and 12.11 %), CaCO3 (49.72; 51.84 and 53.57 %), Si (2.89; 3.53 and 3.43 %), SiO2 (11.02; 11.04 and 9.96), Sr (10.19; 7.52 and 10.03 %) and SrO (12.40; 11.96 and 9.15 %). Ca was found in the form of CaO and CaCO3. The results show that CaCO3 was the highest of mineral content in sediment. It can be concluded that sediment in Karanrang Island can be used as a sample for measuring 14C activity.